Biochemical effects of backpacking with and without counterbalanced load level walking on a treadmill - Safikhani, Hassan (2013)
Backpacks are used every day by students, young and old people to transport items from place to place, but as helpful as they are, if used improperly, they have also been implicated in causing injuries and back pain. When a backpack is overloaded, incorrectly worn, or improperly loaded it can cause a decrease in a person’s performance. So the study intends to investigate the biomechanical effects of backpacking with and without counterbalanced load level walking on a treadmill. The participants of this study were twenty-six male students (Mean Age: 22.41 ± 1.75 years). The walking protocol in this study was walking at 1.5 m/s speed under different conditions (unloaded walking, with normal, and counterbalance backpacks) on the treadmill. Trunk flexion angle, tibialis anterior and latissimus dorsi muscles activity, and ground reaction force, were measured during three conditions. To analyze the data for trunk forward lean angle and ground reaction force throughout a walking cycle with different conditions using a repeated measures ANOVA in SPSS. To analyze the data for tibialis anterior and latissimus dorsi muscles activity one way Analysis of Variance (ANOVA) was used. The results were shown that, there is significant difference among trunk flexion angle in six gait cycles: LR, MS, TS, PS, IS, and TSW, but there is no significant difference in MSW phase between walking with counterbalance backpack condition and unloaded walking. There is also no significant difference between walking with counterbalance backpack and unloaded walking on both muscles activity. There is significant difference among ground reaction force in IC, MS, and TS phases during unloading walking; walking with normal backpack and counterbalance backpack, but there is no significant difference among ground reaction force in LR phase between walking with counterbalance backpack condition and unloaded walking. Findings of this study clearly indicated that the advantage of a counterbalance backpack for carrying the loads. The reduction of forward lean, muscles activity and ground reaction forces is a considerable ergonomic and kinematic benefit of carrying load in such backpacks. Notwithstanding carrying a load may still be considered the major cause of changes to walking patterns or increases in injury rates, the scientific testing of and development of future counterbalance studies can modify these risks. Using a counterbalance backpack may be one such method to reduce these risk.